Leveraging Technology and Innovation for Effective E-Business Management - Syahnur, Haerdiansyah (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The purpose of this study is to examine the multifaceted nature of e-commerce excellence and effective e-business management, with a focus on technological infrastructure, innovation, consumer behavior, and management challenges. Employing a systematic literature review approach, the research design and methodology involve the analysis of recent studies and theoretical frameworks in the field of e-commerce. The findings underscore the critical importance of robust technological infrastructure in driving e-commerce excellence, highlighting the transformative impact of emerging technologies such as artificial intelligence, blockchain, and the Internet of Things. Moreover, the study elucidates the pivotal role of innovation in shaping organizational success, emphasizing the significance of product innovation, process innovation, business model innovation, and organizational innovation. The implications of this study extend to both theory and practice, providing valuable insights for researchers, practitioners, and business leaders in understanding and navigating the complexities of the digital marketplace. By prioritizing investments in digital infrastructure, fostering a culture of innovation, and adopting customer-centric strategies, organizations can position themselves for sustained growth and success in the dynamic e-commerce ecosystem.